Dziecko dwujęzyczne jako uczeń o specjalnych potrzebach edukacyjnych. Słownik dziecka dwujęzycznego – studium przypadku - Barbara Kyrc (Postscriptum Polonistyczne)
The article aims at discussing the situation of a bilingual foreign child at a Polish school and the type of the educational, psychological and pedagogical support that it might receive. The article author proves such child to be a student with special educational needs due to its specific linguistic, social and psychological situation. Both theory and practice suggest that such child’s educational success results above all from its mental vocabulary content. In the case of a bilingual student such vocabulary needs to be competently developed and stimulated.